2019
DOI: 10.1088/1742-6596/1366/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Radiation Effect on MHD Stagnation Point flow of Williamson Fluid over a stretching Surface

Abstract: Thermal radiation effects on MHD stagnation point flow of Williamson fluid over a stretching surface are studied. With the help of similarity transformation, the governing equations are converted to nonlinear ordinary differential equations and then solved numerically by Runge-Kutta-Fehlberg (RKF) technique. Numerical results for the reduced Nusselt number and reduced skin friction coefficient as well as the temperature and velocity profiles are elucidated through tables and graphs. The influence of Prandtl nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Hence increase in buoyancy leads to an increase in the overall velocity of the flow but a decrease in the temperature of the flow. As earlier remarked in the introduction, these results supports the findings of [16,19,20].…”
Section: Discussion Of Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Hence increase in buoyancy leads to an increase in the overall velocity of the flow but a decrease in the temperature of the flow. As earlier remarked in the introduction, these results supports the findings of [16,19,20].…”
Section: Discussion Of Resultssupporting
confidence: 90%
“…Panezai et al [19] examined the influence of thermal radiation on two-dimensional incompressible magneto-hydrodynamic mixed convective heat transfer flow of Williamson fluid flowing past a porous wedge on a non linear stretching surface and the free stream experiencing external forces on the fluid and it was concluded that non -dimensional velocity profile increases with an increase in wedge angle parameter while nondimensional temperature profile decrease with an increase in the wedge angle parameter ,nondimensional velocity deceases with an increase in magnetic parameter. Hashim et al [20]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we extend the earlier model of Hashim et al 35 to consider thermal buoyancy force, porosity, and nonlinear thermal radiation effects on heat transfer due to the stagnation point flow of a Williamson fluid past a stretching sheet. The conservation equations are rendered into a dimensionless form via the similarity transformations.…”
Section: Introductionmentioning
confidence: 97%
“…Also, the pseudoplastic fluid gives effective results when the minimum and maximum viscosities are taken into account in the Williamson fluid model. Various important investigations on the Williamson model, considering vital properties, are available in the literature 27‐38 …”
Section: Introductionmentioning
confidence: 99%